The effects of corn harvested at different stages of maturity and supplemented with urea on silage quality and nutrient digestibility in lambs - Çerçi, IH; Tatli, P; Gürdogan, F; Birben, N (Tubitak Scientific & Technological Research Council Turkey, 2002)
This study was conducted to determine the silage qualities of corn supplemented with urea and harvested at the boot and milk stages and the effect on food intake and nutrient digestibility of these silages in lambs. Corn harvested at the boot and milk stages was supplemented with 0.5% urea and was ensiled. This study involved 4 silage groups. group I consisted of silage from corn harvested at the boot stage; group II consisted of silage from corn harvested at the milk stage; group Ill consisted of silage from corn supplemented with urea and harvested at the boot stage; group IV consisted of silage from corn supplemented with urea at the milk stage. Dry matter levels in the groups were determined to be 18.77, 25.10, 18.82 and 25.20%, respectively. The pH, NH3-N and lactic acid levels of the silages were determined to be 4.16, 4.38, 5.10 and 5.42; 0.48, 0.39, 0.85 and 0.76%; and 1.78,1.96, 1.85 and 2.10% in the groups, respectively. Four 9-month-old Akkaraman male lambs averaging 32 kg live weight were used. The experiment was carried out according to a 2X2 factorial and 4X4 latin square design in individual boxes, Dry matter intakes of lambs were determined to be 557.29, 736.22, 592.33 and 698.39g in the groups, respectively (P<0.01). Dry matter, crude protein and cellulose digestibility were determined to be 67.13, 66.93, 67.27 and 66.25% (P>0.05); 66.34, 65.76, 72.64 and 70.61% (P<0.01); and 64.19, 63.63, 63.53 and 62.91% in the groups, respectively (P>0.05). In this study it was found that corn silage ensiled at the milk stage was higher in quality than at the boot stage. It was determined that silage made from corn supplemented with urea had a positive effect on the food intake and digestibility of crude protein in lambs.
Farkli vejetasyon dönemlerinde hasat edilen misira üre katkisinin silaj kalitesi ve toklularda besin maddelerinin sindirilebilirli?i üzerine etkisi
Keywords: corn; silage; urea; digestibility; lamb